500 years of natural rubber - Baker C S L (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p39)
It wood seem very apt in the quincentennial year of natural rubbers arrival in Europe, from where all modern technology stems, that the history of natural rubbers development should be told. The lecture/paper covers the early historical landmarks of the early days of rubber technology Charles Mackintosh (waterproofing). Thomas Hancock (mastication) Charles Goodyear (vulcanization), and John Boyd Dunlop (pneumatic tyre). It shows some of the early products made from rubber and the first practical means of obtaining rubber from the tree. The story of Wickham follows with his transfer of 1990 seedlings to Sri Lanka in 1876, hence a very apt place for this lecture. A review of some of the early new uses and modified forms of rubber follows, which can be thought of as the middle-ages although some uses exists to this day. Topics covered include Rubber-in-roads (1950), Rubbone (1952), Positex (1952), MG Rubber (1954), First Bridge Bearings?Pelham Bridge (1957) and OENR in Winter Tyres (1967). The talk moves onto modern rubbers (ENR and TPNR) and uses such as truck tyres and earthquake bearings (IRRDB UNIDO projects). Finally it looks to the future with the IRRDB/CFC blends project, world production changes and its long term prospects.
Keywords: Natural rubber; Rubber technology